Moving from an "anti-aging" paradigm toward the concept of "disease-free aging": the role of senolytics in modern medicine - Aprahamian,Ivan (2024)
Senescent cells increase with aging and are related to the promotion of inflammation and neoplasia through the senescence-associated secretory phenotype (SASP). These cells are closely related to the biological aging process and, most importantly, to age-associated diseases, such as osteoporosis and osteoarthritis. Senolytics are a new drug class that kills senescent cells by targeting senescent cell anti-apoptotic pathways (SCAPs), which are biological systems that avoid cellular destruction and host innate defenses. Senolytic therapy requires strong evidence in human trials, and dasatinib and quercetin have shown good results in phase II trials with idiopathic pulmonary fibrosis and diabetic renal disease. However, these trials are small and merely represent a proof-of-concept for these drugs. Nevertheless, this evidence calls for an overview of senescent cells and senolytics. We briefly discuss these related topics, summarizing the best evidence for clinical practitioners.